On the Species Delimitation of the Maddenia Group of Prunus (Rosaceae): Evidence From Plastome and Nuclear Sequences and Morphology - Su, Na; Liu, Bin-bin; Wang, Jun-ru; Tong, Ru-chang; Ren, Chen; Chang, Zhao-yang; Zhao, Liang; Potter, Daniel; Wen, Jun (Frontiers in Plant Science, 2021)
The recognition, identification, and differentiation of closely related plant species present significant and notorious challenges to taxonomists. The Maddenia group of Prunus, which comprises 4–7 species, is an example of a group in which species delimitation and phylogenetic reconstruction have been difficult due to lack of clear morphological distinctions and limited sampling and low informativeness of molecular evidence. Thus, the precise number of species in the group and the relationships among them remain unclear. Here, we used genome skimming to generate DNA sequence data for 22 samples, including 17 Maddenia individuals and five outgroups in Amygdaloideae of Rosaceae, from which we assembled the plastome and 446 single-copy nuclear (SCN) genes for each sample, and reconstructed the phylogenetic relationships of the Maddenia group using both concatenated and coalescent-based methods. We also identified eight highly variable regions and detected simple sequence repeats (SSRs) and repeat sequences in the Maddenia species plastomes. The phylogenetic analysis based on complete plastomes strongly supported three main subclades in the Maddenia group of Prunus, while five subclades were recognized based on the nuclear tree. The phylogenetic network analysis detected six hybridization events. Integrating nuclear and morphological evidence, we proposed to recognize five species within the Maddenia group, i.e., Prunus fujianensis, P. himalayana, P. gongshanensis, P. hypoleuca, and P. hypoxantha. Within this group, the first three species are well supported, while gene flow, occurring throughout the Maddenia group, seems to be especially frequent between P. hypoleuca and P. hypoxantha, eroding the barrier between them. Phylogenetic trees based on eight concatenated hypervariable regions had a similar topology with that of complete plastomes, showing their potential as molecular markers and effective barcodes for further phylogeographic studies of Maddenia.